2017
DOI: 10.1128/jvi.02211-16
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Sensitive Live-Attenuated Canine Influenza Virus H3N8 Vaccine

Abstract: Canine influenza is a respiratory disease of dogs caused by canine influenza virus (CIV). CIV subtypes responsible for influenza in dogs include H3N8, which originated from the transfer of H3N8 equine influenza virus to dogs; and the H3N2 CIV, which is an avian-origin virus that adapted to infect dogs. Influenza infections are most effectively prevented through vaccination to reduce transmission and future infection. Currently, only inactivated influenza vaccines (IIVs) are available for the prevention of CIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(83 citation statements)
references
References 76 publications
5
78
0
Order By: Relevance
“…1B). Both combinations of plasmids (WT and LAIV) resulted in similar Gaussia luciferase (Gluc) expression levels at 33°C; however, Gluc expression was significantly reduced at higher temperatures (37°C and 39°C) in cells transfected with the pH1N1 LAIV plasmids, consistent with previous results shown for other IAV LAIV strains (9)(10)(11). Importantly, Western blot analysis shows similar levels of NP expression at each temperature for WT-and LAIV-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…1B). Both combinations of plasmids (WT and LAIV) resulted in similar Gaussia luciferase (Gluc) expression levels at 33°C; however, Gluc expression was significantly reduced at higher temperatures (37°C and 39°C) in cells transfected with the pH1N1 LAIV plasmids, consistent with previous results shown for other IAV LAIV strains (9)(10)(11). Importantly, Western blot analysis shows similar levels of NP expression at each temperature for WT-and LAIV-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 79%
“…In order to generate a pH1N1 LAIV virus, we introduced four ts mutations identified in previous studies into the PB2 (N265S) and PB1 (K391E, D581G, and A661T) ORFs of pH1N1 (Fig. 1A) (7,9,10,39). No mutation was introduced into the viral NP, since pH1N1 NP already contains a G at position 34.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid residues conferring these ts, ca, and att phenotypes have been mapped for both viruses and share no residues in common, although they fall almost exclusively into the genes encoding viral RNAdependent RNA polymerase (28,29). Moreover, our group and others have introduced the mutations responsible for the ts and att phenotype of AA/60 H2N2 into different IAV subtype and strain backgrounds and have shown that they confer a ts phenotype in cell culture and an att phenotype in animal models (30)(31)(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%